Comparison of image quality using a X-ray stereotactical whole-body system and a direct flat-panel X-ray device in examinations of the pelvis and knee - Krug, K. B.; Weber, C.; Schwabe, H.; Sinzig, N.-M.; Wein, B.; Müller, D.; Wegmann, K.; Peters, S.; Sendler, V.; Ewen, K.; Hellmich, M.; Maintz, D. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: The novel biplanar X-ray unit “EOS”, EOS Imaging, allows to acquire simultaneously 2 perpendicular planes of full-length spine and limbs and to measure spatially correct angles based on the acquired image data sets. This is to be seen alongside with a low spatial resolution, high investment costs and high operating expenses. The use of the biplanar X-ray unit in morphology based scelettal radiography might improve the cost-benefit-relation. Thus, the purpose of this study was to compare image quality of the EOS-unit and the flat panel (FP)-technology as reference in a clinical setting.Materials and Methods: All 114 patients of the Orthopedic Hospital Dept., who had a biplanar full-length lower limb radiograph and a FP-examination of the pelvis and/or the knee with maximum time interval of 3 months without changes in the clinical and radiological findings were included in the study. All X-ray examinations had been carried out due to clinical indications. Secondary captures comparable to the FP-images were extracted from the electronic EOS-image data sets. 4 radiologists independently from each other compared the visualization of normal anatomical structures of the pseudonymous EOS- and FP-images in a randomized order.Results: In the overwiew of all readers and all sceletal regions image quality of the FP-images was considered being superior in a mean of 83 ± 13 % standard deviation of the pair comparisons (minimum 48 %, maximum 100 %). Image quality of the EOS-images was assessed as being superior in 2 ± 3 % of the cases (0 %, 10 %). Image quality of 0.8 ± 3 % of the FP-images (0 %, 17 %) and 30 ± 34 % (0 %, 100 %) of the EOS-images was estimated as diagnostically inadequate. 30 ± 33 % of the pair comparisons (0 %, 100 %) showed a diagnostically inadequate image quality of the EOS-images and a diagnostically good image quality of the FP-images.Conclusion: Image quality of biplanar full-length lower limb X-ray examinations is not suitable to be used for the diagnostic assessment of the morphological bone structure using the currently available technological setting.Key points:Citation Format:
Keywords: skeletal-axial; extremities; digital radiography; technology assessment